Antibacterial and Non-Cytotoxic Effect of Nanocomposites Based in Polyethylene and Copper Nanoparticles - Rabagliati-Canessa, F; Paez-Collio, M; Paez-Collio, M; Azocar-Guzman, M; Azocar-Guzman, M; Tamayo-Villarroel, L; Tamayo-Villarroel, L; Muñoz-Moena, L; Muñoz-Moena, L; Zapata-Ramirez, P (Kluwer Academic Publishers, 2015)
Abstract: In this study, an antibacterial, but not cytotoxic nanomaterial based on polyethylene and copper nanoparticles was prepared by in situ polymerization. PE–CuNps nanocomposites against Escherichia coli, completely suppressed the number of live bacteria after 12 h incubation compared to neat PE. TEM images showed that nanocomposites damage the plasma membrane of the bacteria, revealing a bacteriolytic effect. Toxic effects of copper nanoparticles on viability of neuroblastoma line cell also was evaluated, revealing a non cytotoxic effect for the doses used, showing that this nanocomposite is a ideal material for medical devices.Graphical Abstract: [Figure not available: see fulltext.] © 2015, Springer Science+Business Media New York.